2017
DOI: 10.1016/j.sjpain.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygenation alleviates chronic constriction injury (CCI)-induced neuropathic pain and inhibits GABAergic neuron apoptosis in the spinal cord

Abstract: Increased apoptotic GABAergic neurons induced by activation of key proteins of mitochondrial apoptotic pathways in the dorsal horn of the spinal cord is critical in CCI-induced neuropathic pain. The inhibitory role of HBO in GABAergic neuron apoptosis suppresses ongoing neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 54 publications
1
34
0
1
Order By: Relevance
“…In addition, the effect of Sal B on neural cell apoptosis was evaluated. Induction of cell apoptosis, which enhances the loss of neurons and reduces neuronal functional recovery, has been widely reported following SCI (26,27). In the present study, western blot analysis determined that the expression levels of Bax, cleaved caspase-3 and cleaved caspase-9 were increased in spinal cord tissues following SCI but the expression of Bcl-2 decreased.…”
Section: Discussionsupporting
confidence: 47%
“…In addition, the effect of Sal B on neural cell apoptosis was evaluated. Induction of cell apoptosis, which enhances the loss of neurons and reduces neuronal functional recovery, has been widely reported following SCI (26,27). In the present study, western blot analysis determined that the expression levels of Bax, cleaved caspase-3 and cleaved caspase-9 were increased in spinal cord tissues following SCI but the expression of Bcl-2 decreased.…”
Section: Discussionsupporting
confidence: 47%
“…Impaired tissue oxygen saturation in patients with CRPS 1 [ 50 ] may be associated with pain levels in CRPS. Indeed, hyperbaric oxygen therapy significantly alleviated mechanical allodynia, suggesting the inhibitory role of hyperbaric oxygen therapy in GABAergic neuron apoptosis suppresses ongoing neuropathic pain [ 51 ]. In other words, while high levels of oxygen may reduce pain levels, high CO 2 levels may increase sensory pain levels, affecting the synergic boost of neuropsychiatric symptoms such as depression, anxiety and suicidal ideation in CRPS patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, HBOT must be administered during the small reperfusion window, which creates a limited opportunity for effective treatment. This has been a reoccurring problem with HBOT because of the difficulty associated with determining the reperfusion window and extensive imaging to determine the appropriate course of action [ 15 ]. Evidently, some studies indicate that delayed HBOT past the effective window of treatment actually causes worse outcomes.…”
Section: Hbot In Ischemic Stroke: Potential Benefits and Limitatiomentioning
confidence: 99%
“…HBOT is highly effective when administered 30 to 60 min after stroke, and the potency of treatment lessens if initiation is delayed any further. HBOT exhibits therapeutic potential in its ability to reduce infarct volume and improve behavioral scores in patients [ 14 , 15 ]. Research has demonstrated different time points at which HBOT is effective, such as HBOT (2.5 ATA for 2 h) at 6 h after reperfusion [ 35 ], and HBOT (3 ATA, 1 h) at 3 and 6 h after reperfusion [ 36 ].…”
Section: Hbot In Ischemic Stroke: Potential Benefits and Limitatiomentioning
confidence: 99%